Antecedent Factors Affecting the Quality of Village Funding Reports Information - Budiarto, Dekeng Setyo; Oviana, Krismonita; Suparjito, Suparjito (FEB Universitas Sultan Ageng Tirtayasa, 2024)
Researchers are interested in studying the accountability of village money management because there is still fraud involving village officials. The antecedent elements that affect fraud prevention in the financial management of village funds are examined in this study. The impact of fraud prevention on the accuracy of the information in village fund financial reports is also examined in this study. 22 villages in Bantul Regency received questionnaires as part of the research project. 51 respondents, who were members of the village machinery responsible for creating financial reports for the village fund, responded to the questionnaires after they were distributed. Convenience sampling was used in the sampling process. In this work, smart PLS was used to examine structural techniques for data analysis. Increasing competence, control, and morality have an impact on preventing fraud in the financial administration of village funds, and preventing fraud has an impact on the quality of information on village fund reports, according to the research's findings. The findings of this study have significance for village governments to raise the standard of their human resources and oversight to enhance village finance management